Penerapan Pengendalian Internal Penerimaan Dana Kurban Dan Pembelian Hewan Kurban Di Masjid Baiturrahman - Putra, Idrisi Raliya; Hidayatullah, Syarif; Tahang, Moh; Saputri, Haria; Azzahra, Sitti Aliyah (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2024)
Baiturrahman Mosque is a PKM partner that facilitates the implementation of sacrifices which have been carried out for approximately 25 years. In this PKM activity, the team brought up a big topic, namely good and healthy management of sacrificial animals. To support this topic, researchers evaluated the implementation of internal control over the receipt of sacrificial funds and the purchase of sacrificial animals at the Baiturrahman Mosque using a qualitative descriptive implementation method. In carrying out the evaluation, researchers collected data by means of observation and interviews. Primary data in the form of internal control of receiving sacrificial funds and internal control of purchasing sacrificial animals was obtained through questions and answers with Mr. Ajat, Mr. Sugeng, and Mr. Sarkum as chairman and members of the Baiturrahman Mosque's sacrificial committee. Based on the data collected, researchers found that the implementation of internal control in the implementation of sacrificial worship activities at the Baiturrahman Mosque in 2024 still needs to be optimized because it has not considered/controlled the following things: 1. Organizational structure that has not been well documented, 2. Evidence of receipt of sacrificial funds and purchase of sacrificial animals, the serial number is still written manually and has not been printed, 3. The sacrificial fund account is not yet separate from the mosque fund account, 4. Bank reconciliation has not been carried out considering that funds are also received by transfer, 5. There is no rotation of both buyers and suppliers of sacrificial animals